2014
DOI: 10.1142/s021759081450026x
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Property Bubbles in Hong Kong and Singapore: Another Aftershock Crisis of the Global Financial Tsunami?

Abstract: This paper first provides a brief review of the global financial tsunami. It then explains why the quantitative easing in the US and the unique characteristics of the Asian property markets have contributed to the formation of property bubbles in some Asian economies. Thereafter, it discusses the possibility of a bursting of property bubbles in Hong Kong, Singapore or another Asian economy a few years from now, and highlights that the bursting of the property bubble in that economy could trigger severe correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Notably, they emphasized the significance of abrupt reversals in investment streams, self-propagating anticipations that had accumulated within the afflicted economies preceding the crisis. Yip [7] contributed to the discourse by underscoring the impact of speculative attacks by hedge funds as a triggering factor and by emphasizing the significance of asset bubbles as another pivotal underlying cause of the crisis. For the case of the Chinese stock market bubble, Paul [8] and Ken-ichi [9] provided a detailed discussion of the formation and subsequent burst of the 2006-08 parent stock bubble, Tsomaia and Akaki [10] and Miao Jianjun and Wang Pengfei [11] delved into the warrants bubble during the same timeframe, while Liu, Gu, and Rui Huang [12] discussed the 2014-15 stock market bubble.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, they emphasized the significance of abrupt reversals in investment streams, self-propagating anticipations that had accumulated within the afflicted economies preceding the crisis. Yip [7] contributed to the discourse by underscoring the impact of speculative attacks by hedge funds as a triggering factor and by emphasizing the significance of asset bubbles as another pivotal underlying cause of the crisis. For the case of the Chinese stock market bubble, Paul [8] and Ken-ichi [9] provided a detailed discussion of the formation and subsequent burst of the 2006-08 parent stock bubble, Tsomaia and Akaki [10] and Miao Jianjun and Wang Pengfei [11] delved into the warrants bubble during the same timeframe, while Liu, Gu, and Rui Huang [12] discussed the 2014-15 stock market bubble.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kong, Yip [27] highlighted the high likelihood of an eventual bursting of the gigantic property bubble in Hong Kong, which could in turn trigger another Asian Financial Crisis through the contagion effect. After extending the analysis to the property markets in other East Asian economies, Yip [28] concluded that another Asian financial crisis would be a question of time instead of whether-or-not.…”
Section: After a Detailed Analysis Of The Property Bubble And Curbingmentioning
confidence: 99%
“…Firms also used huge amount of company money and/or borrowed huge amount of money for shares investment. Similarly, according to Yip [27] [28], during all the three stages of Hong Kong's property bubble between early 2009 and 2018, the increase in the speculative demand, investment demand and then panic demand was so enormous that the property price index has more than tripled during that period.…”
Section: The Development Stagementioning
confidence: 99%
See 1 more Smart Citation